Blockchain and its applications (B) - Mohamed Ajmal Abdul Jabbar (Nanyang Technological University, 2021)
In the financial industry, every transaction made by the customer must be verified by the customer themselves. This is to ensure that the person who is making the transaction is the person authorised to do so. Some transactions and policies could be made by phone, over a telecommunication network. Banks usually record the entire conversation between the bank and the customer. Unfortunately, this type of verification is not trustworthy, as there is no confirmation that the customer on the other end is the right user.